PATRIARCHY AND STEREOTYPES: THE CHALLENGES OF WOMEN'S CONTRIBUTION IN INDONESIAN POLITICS - Palimbunga, Marvill Jonathan (Universitas Padjadjaran, 2024)
Although there are several women in politics, there still needs to be more women who contribute to politics. The representation of women in Indonesian politics is still under 30% and ranked 7th in Southeast Asia. Mostly, it is because women are always portrayed as figures who are not qualified to take the lead. Taking the viewpoint based on their physics, women are totally different and not as strong as men and for that reason, there are perceptions that politics are only meant for males, not females. At the same time, women participants are essential and required to create women-friendly policies as the women are portrayed as individuals who are doubted to take the lead. They are considered unqualified to be in politics, and their presence is seen as a complement. The perceptions toward women that have been created have become a challenge for women in politics. In this study research, the readers will figure out the culture of the patriarchal system in Indonesia leads to stereotypes towards women that make it difficult for women to participate in politics actively. Also, this research aims to determine the treatment differences between women in the United Arab Emirates. The analysis indicated that mostly society is still stereotyping women as those who are not qualified to participate in politics is not due to the patriarchal system that puts women as subordinates. Still, it is also because of the women themselves. They already feel comfortable in a traditionalist system and tend to let men lead some projects because they think men must lead an event or activity. Mostly, women behave as someone who needs to be qualified to take the lead.